Modeling of a square-shape ZnO, ZnS and AlN membrane for mems capacitive pressure-sensor applications - Dagamseh Ahmad; Al-Bataineh Qais; Al-Bataineh Zaid; Daoud Nermeen S.; Alsaad Ahmad; Omari Ahmad (International Journal for Simulation and Multidisciplinary Design Optimization, 2020)
In this paper, mathematical modeling and simulation of a MEMS-based clamped square-shape membrane for capacitive pressure sensors have been performed. Three types of membrane materials were investigated (i.e. Zinc Oxide (ZnO), Zinc Sulfide (ZnS) and Aluminum Nitride (AlN)). Various performance parameters such as capacitance changes, deflection, nonlinearity, the sensitivity of the membrane structure for different materials and film-thicknesses have been considered using the Finite Element Method (FEM) and analytically determined using the FORTRAN environment. The simulation model outperforms in terms of the effective capacitance value. The results show that the membrane deflection is linearly related to the applied pressure. The ZnS membrane provides a capacitance of 0.023 pico-Farad at 25 kPa with a 42.5% relative capacitance changes to reference capacitance. Additionally, the results show that for ZnO and AlN membranes the deflection with no thermal stress is higher than that with thermal stress. However, an opposite behavior for the ZnS membrane structure has been observed. The mechanical and capacitance sensitivities are affected by the membrane thickness as the capacitance changes are inversely proportional to the membrane thickness. Such results open possibilities to utilize various materials for pressure sensor applications by means of the capacitance-based detection technique.